A Pattern Reconfigurable Antenna Based on TM10 and TM02 Modes of Rectangular Patch - Huang, Hai-Yan; Wang, Bing-Zhong; Ding, Xiao; Shao, Wei (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A pattern reconfigurable rectangular microstrip antenna is reported in this paper. A broadside radiation pattern and a conical pattern are obtained when it alternatively operates in the TM10 mode and TM02 mode of the rectangular patch. Suitable patch size parameters and feeding positions are selected so that these two modes share the same operating frequency. Two PIN diodes are employed to switch the operating modes. The configuration of the antenna is simple, which consists of a rectangular patch and a reconfigurable feeding network to excite expected mode. The feature of the proposed antenna is that the design method is explicit, based on different resonant modes with different radiation characteristics, and can be used to design other types of reconfigurable antennas